2001
DOI: 10.1034/j.1600-0609.2001.067001045.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hepatitis virus infection and severe liver dysfunction in patients receiving chemotherapy for hematologic malignancies

Abstract: Hepatitis virus infection through virus reactivation has a high risk of mortality in patients with hematological malignancies receiving chemotherapy. We examined the incidence of both hepatitis B virus (HBV) and hepatitis C virus (HCV) infection and severe liver dysfunction (alanine aminotransferase >ten times the normal upper limit and total bilirubin >5 mg/dl) during chemotherapy in 268 patients with hematological malignancies. Eight patients (3.0%) were infected with HBV and 22 patients (8.2%) were infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
3
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 18 publications
2
65
3
7
Order By: Relevance
“…[1][2][3] These reactivations have been observed, especially in hepatitis B surface antigen (HBsAg)-positive subjects 4 and they occur in 20%-50% of cases, with a mortality rate of 10%-40%. Consequently, lamivudine prophylaxis is strongly recommended in HBsAg-positive subjects receiving chemotherapy or immunosuppressive therapy, [5][6][7] although there are no clear guidelines for HBsAg-negative subjects.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These reactivations have been observed, especially in hepatitis B surface antigen (HBsAg)-positive subjects 4 and they occur in 20%-50% of cases, with a mortality rate of 10%-40%. Consequently, lamivudine prophylaxis is strongly recommended in HBsAg-positive subjects receiving chemotherapy or immunosuppressive therapy, [5][6][7] although there are no clear guidelines for HBsAg-negative subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Such a condition due to HBV reactivation in the HBs antigen or HBV-DNA negative state is referred to as de novo hepatitis B. [4][5][6] A study conducted in Japan has recently demonstrated the higher incidence of de novo hepatitis B becoming fulminant hepatitis than of the common acute hepatitis B with a higher mortality rate. [7] And also, the guideline for the prevention and treatment of HBV reactivation during immunosuppressive drug therapy was developed by the Clinical Practice and Quality Measures Committee (currently the Clinical Practice Guideline Committee) and approved by the AGA Governing Board.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that, even in this state, some patients develop fatal severe hepatitis owing to HBV reactivation following immunosuppressive therapy for the treatment of various diseases including cancer, autoimmune disease, and organ transplant and that this hepatitis has been referred to as de novo hepatitis B. [4][5][6] Because the rates of fulminant hepatitis B and fatal hepatitis B are high among de novo hepatitis patients, [7] a careful follow-up is also recommended for patients with a resolved HBV infection and who underwent immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,12 However, 7-30% of the HCV-positive lymphoma patients experience HCV related hepatotoxicity secondary to chemotherapy. 6 In a study, liver enzyme abnormalities during chemotherapy for malignancies were seen in 54% of the HCV-positive patients, and in 34% of the HCV-negative patients.…”
Section: Discussionmentioning
confidence: 99%